Genome-wide analysis of LTR-retrotransposons in oil palm. (December 2015) - Beulé, Thierry; Agbessi, Mawussé; Dussert, Stephane; Jaligot, Estelle; Guyot, Romain
Abstract Background The oil palm (Elaeis guineensis Jacq.) is a major cultivated crop and the world's largest source of edible vegetable oil. The genusElaeis comprises two speciesE. guineensis, the commercial African oil palm andE. oleifera, which is used in oil palm genetic breeding. The recent publication of both the African oil palm genome assembly and the first draft sequence of its Latin American relative now allows us to tackle the challenge of understanding the genome composition, structure and evolution of these palm genomes through the annotation of their repeated sequences. Methods In this study, we identified, annotated and compared Transposable Elements (TE) from the African and Latin American oil palms. In a first step, Transposable Element databases were built throughde novo detection in both genome sequences then the TE content of both genomes was estimated. Then putative full-length retrotransposons with Long Terminal Repeats (LTRs) were further identified in theE. guineensis genome for characterization of their structural diversity, copy number and chromosomal distribution. Finally, their relative expression in several tissues was determined throughin silico analysis of publicly available transcriptome data. Results Our results reveal a congruence in the transpositional history of LTR retrotransposons betweenE. oleifera andE. guineensis, especially theSto-4 family. Also, we have identified and described 583 full-length LTR-retrotransposons in theElaeis guineensis genome. Our work shows that these elements are most likely no longer mobile and that no recent insertion event has occurred. Moreover, the analysis of chromosomal distribution suggests a preferential insertion ofCopia elements in gene-rich regions, whereasGypsy elements appear to be evenly distributed throughout the genome. Conclusions Considering the high proportion of LTR retrotransposon in the oil palm genome, our work will contribute to a greater understanding of their impact on genome organization and evolution. Moreover, the knowledge gained from this study constitutes a valuable resource for both the improvement of genome annotation and the investigation of the evolutionary history of palms.